Convergence and fragmentation : media technology and the information society - Ludes, Peter (Changing media--changing Europe series ;, 2008)
A collection of articles which analyze the technological, economic, and political trends sweeping Europe. It also assesses the effectiveness of models used to explain the changing media environment.